Cultural Values In The Film 'Najih' By Pondok Pesantren Dalwa Charles Sanders Peirce's Semiotic Analysis - Hartono, Alfina; Rohanda, Rohanda; Fauziah, Isma (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2024)
This research aims to describe the cultural values contained in the film